How different training sessions affect the sleep of professional soccer players - Eider Barba; David Casamichana; Julen Castellano (Biology of Sport)
This study aimed to compare microcycle loading and sleep patterns concerning successive match days (MD) using objective measurements of sleep and external training load (eTL). Twenty professional female soccer players (mean age: 23.3±3.5 years) were monitored using a multi-sensor sleep-tracker for sleep patterns and global positioning system devices for eTL. Sleep variables included total sleep time (TOTAL), awake time (AWAKE), REM sleep, deep sleep time (DEEP), light sleep time (LIGHT), percentage of sleep time spent moving (REST), and sleep onset latency (ONSET). eTL variables included total distance covered (TD), distance at various speed thresholds, accelerations (ACC3), and decelerations (DEC3). 1) eTL influenced sleep; 2) TOTAL and REM were reduced after high eTL sessions (MD-3); 3) MD-2 facilitated recovery and improved post-session sleep compared to MD-4 and MD-3; 4) post session TOTAL and DEEP sleep times on MD-1 were shorter compared to pre-session times, but there was no difference in REM sleep. Additionally, DEEP had a negative correlation with eTL variables, while REST had a positive correlation with certain eTL variables. REM sleep was affected after high eTL sessions, indicating that fatigue negatively impacted sleep. However, sleep increased after lower eTL sessions. Players slept less with less DEEP sleep the day before a competition (MD-1 post-session sleep). Monitoring sleep during microcycle acquisition and loading phases could assess sleep changes. Strategies should be implemented to improve sleep during loading phases and the night before matches.